Successfully Achieving Strategy Through Effective Portfolio Management. - Parth, Frank R. (New York : Business Expert Press, 2021)
This book provides the approach that significantly increases an organization's ability to achieve its strategy. This is not a book about developing strategy. This is a book that will help you actually achieve the strategy the organization's leadership has developed. Strategy is necessary but it is a complete waste of time unless it is effectively turned into real results. If you want to see where an organization will be in 5 years, don't look at its strategic goals. Look at where management spends the money.
Cover -- Halftitle -- Title -- Copyright -- Description -- Contents -- Preface -- Step 1: Prepare the Organization -- Step 2: Designing the Enterprise-Level Portfolio Management System -- Step 3: Planning and Implementing the EPMS -- Appendices -- Notes -- References -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Strategic planning; Organizational change--Management.; Industrial management; Electronic books